Leadership practices that support effective teaching and learning : learning from the Eastern Cape rural schools - Gogo, Desmond Monde; Mkhize, Bongani Nhlanhla; Bhengu, Thamsanqa Thulani (African Perspectives of Research in Teaching & Learning (APORTAL), 2022)
The study was conducted in four purposively selected secondary schools in O.R. Tambo District in the Eastern Cape. Selected schools had demonstrated exponential improvement in their exit classes in the past five years. Since rural based schools had attracted negative attention for poor academic achievement, we became interested in understanding what these schools, that received recognition for good performance, were doing right. In view of improved academic performance achieved, we sought to elicit insights about what had worked well for these schools. We adopted a qualitative case study approach, within an interpretive paradigm to generate data. We adopted Weber’s Instructional Leadership model to analyse the findings from the participants. Utilising semi-structured interviews and documents’ reviews, within a qualitative design, we generated data from principals, deputy principals and two departmental heads per school. Our analysis generated four themes that characterised their leadership practices. Some of the practices had some characteristics that are uniquely rural. We recommend that these unique leadership practices be explored further on a large-scale study for generalisability about how other School Management Team members can support effective teaching and learning in some adverse and turbulent rural contexts.
Journal article published in African Perspectives of Research in Teaching & Learning Journal (APORTAL) Vol 6 (2) (2022) 250
Keywords: Leadership; Rurality; Traditional leadership; Successful leadership; Leadership; School management teams; Effective teaching -- South Africa -- Eastern Cape; Academic achievement